Praktik Pembatasan Pembalikan Beban PembuktianDalam Pengadilan Tipikor(Studi Pada Perkara Korupsi Rapbd Kota SemarangDi Pengadilan Tipikor Kota Semarang) - Mulyanto, Mulyanto (2016)
Reversal of the burden of proof in a criminal act of corruption has been in effect since 1960, then entered the positive law in 1971, 1999 jo Law No. 20/2001. Until now, this system has not run affective, because it is constrained by several factors. The main obstacle was more due to the regulations between the criminal law. This system does not apply equally to all corruption offenses, applies only to certain offenses it exists in the law 20 of 2001. This research is juridical empirical, ie see the rule of law and the reality that occurs in the process of criminal justice corruption in high court city of Semarang. Resources are the law, law books and journals, interviews with judges, lawyers and legal experts. analyzes using trigulasi system to avoid subjectivity researchers. This research resulted in the conclusion that the reversal of the burden of proof only applies to the corruption of all the offense that led to the loss of money and wealth of the country/ region. later proved to be rich because of corruption. otherwise if such actions are not causing the state losses do not apply to him the reversal of the burden of proof.